KETERLIBATAN DAN PERTANGGUNGJAWABAN PEJABAT PEMBUAT AKTA TANAH DALAM PEMBUATAN AKTA YANG DIJADIKAN ALAT BUKTI PADA PUTUSAN NOMOR 537K/Pid.Sus/2014 - Victoria Maria Johanna (Jurnal Riset Multidisiplin Edukasi, 2026)
Deeds drawn up by Land Deed Officials (Pejabat Pembuat Akta Tanah/PPAT) constitute authentic instruments possessing full evidentiary value and play a crucial role in land registration and the transfer of land rights. Nevertheless, procedural irregularities in the preparation of PPAT deeds may render such deeds instruments facilitating the commission of money laundering offences. This article examines the legal framework governing the validity of PPAT deeds under Government Regulation Number 37 of 1998 in conjunction with Government Regulation Number 24 of 2016, and analyses the involvement and liability of PPATs in the preparation of deeds used as evidence in money laundering cases, as reflected in Supreme Court Decision Number 537 K/Pid.Sus/2014. This research employs a normative juridical method with a statutory and case approach. The findings indicate that although the material requirements of a legal transaction may be fulfilled, violations of formal requirements—such as non-compliance with territorial authority, the use of blank deed forms, and the absence of the parties at the time of execution—may deprive a PPAT deed of its authentic character and expose the PPAT to administrative, civil, and, under certain circumstances, criminal liability. Criminal liability may arise where it is proven that the PPAT acted intentionally or actively participated in facilitating money laundering. Accordingly, this article recommends strengthening administrative supervision over PPATs and reinforcing the principle of due diligence in the preparation of land deeds as preventive measures against money laundering in the land sector.